A Systematic Literature Review on Hybrid Learning Management Systems: Research Gaps and Model Design - Rofiuddin Rofiuddin; Fitri Aulia (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study aims to systematically examine literature related to the development of hybrid Learning Management Systems (LMS), focusing on system integration models, cross-platform usability aspects, and their effectiveness in supporting student engagement and learning outcomes. The review was conducted using a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Out of a total of 1,342 identified publications, 25 studies met the inclusion criteria and were analyzed further.The synthesis results indicate that hybrid LMS integration is still largely dominated by technical approaches, such as the use of APIs, interoperability standards, and hybrid recommendation systems. However, most studies have not yet fully incorporated pedagogical principles into the system design. Usability analysis reveals that web platforms tend to be more capable of supporting complex learning activities, while mobile platforms offer flexibility but are limited by deeper navigation structures and interface consistency challenges.In terms of effectiveness, several studies reported increased engagement and support for adaptive learning, although empirical evidence regarding impacts on learning outcomes remains limited. Overall, the success of hybrid LMS depends on alignment between technical integration, UX design, and pedagogical needs. Future research is recommended to develop and evaluate hybrid LMS prototypes that meaningfully integrate structured and self-directed learning, conduct in-depth cross-platform usability evaluations, and explore hybrid LMS models that incorporate artificial intelligence (AI) as an adaptive component within the learning process.